The occupational and personal stress among the heads and coordinators of the departments in the university and its relation with some scientific and social variables - Mohammad, Nasraddin (Humanities Journal of University of Zakho, 2023)
The aim of study is to testify the statistical meaning concerning the significant differences between the occupational and personal stress among the heads and coordinators of the departments in the University of Zakho in the Iraq- Kurdistan region according to the variables of the study. The population and the sample of the research consists of (42) heads and coordinators of the departments. The researcher used a prepared questionnaire by (Saeed, 2006) include of (40) items. After using (SPSS), results of the research showed that members of research's sample don't feel occupational and personal stress; also there are not statistical significant differences between their opinions about study's main variables; and also results showed that there is a direct and deep relationship between study's two main aspects.